Review of development of an instrumentation system for measuring tractive performance of tractor - Babalola, A. A.; Adisa, A. F.; Aderinlewo, A. A.; Adesodun, J. K. (НУБіП України, 2023)
Представлені тези доповідей науково-педагогічних працівників, наукових співробітників, аспірантів та студентів НУБіП України, провідних вітчизняних і закордонних вищих навчальних закладів та наукових установ, в яких розглядаються завершені етапи розробок.

The Proceedings presents abstracts of reports of scientific and pedagogical workers, research staff, graduate students and students of the NULES of Ukraine, leading domestic and foreign higher educational institutions and scientific institutions, in which completed stages of development are considered.
Keywords: development of an instrumentation system; instrumented system; performance of tractors in field operations; developed a computer-based system; microcomputer and microelectronics-based system